Supermassive population III supernovae and the birth of the first quasars - Whalen, Daniel J.; Even, Wesley; Smidt, Joseph; Heger, Alexander; Chen, K.-J.; Fryer, Chris L.; Stiavelli, Massimo; Xu, Hao; Joggerst, Candace C. (The astrophysical journal, 2013)
The existence of supermassive black holes as early as z ∼ 7 is one of the great, unsolved problems in cosmological structure formation. One leading theory argues that they are born during catastrophic baryon collapse in z ∼ 15 protogalaxies that form in strong Lyman-Werner UV backgrounds. Atomic line cooling in such galaxies fragments baryons into massive clumps that are thought to directly collapse to 104-105 M☉ black holes. We have now discovered that some of these fragments can instead become supermassive stars that eventually explode as thermonuclear supernovae (SNe) with energies of ∼1055 erg, the most energetic explosions in the universe. We have calculated light curves and spectra for supermassive Pop III SNe with the Los Alamos RAGE and SPECTRUM codes. We find that they will be visible in near-infrared all-sky surveys by Euclid out to z ∼ 10-15 and by WFIRST and WISH out to z ∼ 15-20, perhaps revealing the birthplaces of the first quasars.